"It's Like Power to Move": Black Students' Psychosocial Experiences in Black Studies Courses at a Predominantly White Institution. Issue 2 (6th April 2018) - Chapman‐Hilliard, Collette; Beasley, Samuel T.
Abstract : This study examined Black students' experiences in culture‐centered courses that focused on the historical and contemporary experiences of Blacks in America and across the African diaspora. Using a qualitative approach, the authors investigated the perceptions of how Black Studies courses shaped the psychosocial experiences and identity development of Black students ( N = 24) at a predominantly White institution. Data from semistructured focus group interviews revealed several themes, including psychological empowerment, self‐determination, counterspaces, and community perpetuity. The authors suggest ways counselors and educators can support Black students' psychosocial development and provide outreach to diverse student populations. Este estudio examinó las experiencias de estudiantes negros en cursos centrados en la cultura que se enfocaron en las experiencias históricas y contemporáneas de personas negras en Estados Unidos y a lo largo de la diáspora africana. Usando un enfoque cualitativo, los autores investigaron las percepciones sobre cómo los cursos de Cultura Negra dieron forma a las experiencias psicosociales y al desarrollo de la identidad de estudiantes negros ( N = 24) en una institución predominantemente blanca. Los datos obtenidos de entrevistas semiestructuradas en grupos de enfoque revelaron varios temas que incluyen el empoderamiento psicológico, la autodeterminación, los espacios seguros y la perpetuidad de la comunidad. Los autores sugieren distintas formas en las que los consejeros y educadores pueden apoyar el desarrollo psicosocial de los estudiantes negros y proporcionar un acercamiento a poblaciones diversas de estudiantes.